Small RNA sequencing and degradome analysis of developing fibers of short fiber mutants Ligon-lintles-1 (Li1) and −2 (Li2) revealed a role for miRNAs and their targets in cotton fiber elongation. (December 2016) - Naoumkina, Marina; Thyssen, Gregory; Fang, David; Hinchliffe, Doug; Florane, Christopher; Jenkins, Johnie
Abstract Background The length of cotton fiber is an important agronomic trait that directly affects the quality of yarn and fabric. Understanding the molecular basis of fiber elongation would provide a means for improvement of fiber length. Ligon-lintless-1 (Li 1 ) and −2 (Li 2 ) are monogenic and dominant mutations that result in an extreme reduction in the length of lint fiber on mature seeds. In a near-isogenic state with wild type cotton these two short fiber mutants provide an effective model system to study the mechanisms of fiber elongation. Plant miRNAs regulate many aspects of growth and development. However, the mechanism underlying the miRNA-mediated regulation of fiber development is largely unknown. Results Small RNA libraries constructed from developing fiber cells of the short fiber mutantsLi 1 andLi 2 and their near-isogenic wild type lines were sequenced. We identified 24 conservative and 147 novel miRNA families with targets that were detected through degradome sequencing. The distribution of the target genes into functional categories revealed the largest set of genes were transcription factors. Expression profiles of 20 miRNAs were examined across a fiber developmental time course in wild type and short fiber mutations. We conducted correlation analysis between miRNA transcript abundance and the length of fiber for 11 diverse Upland cotton lines. The expression patterns of 4 miRNAs revealed significant negative correlation with fiber lengths of 11 cotton lines. Conclusions Our results suggested that the mutations have changed the regulation of miRNAs expression during fiber development. Further investigations of differentially expressed miRNAs in theLi 1 andLi 2 mutants will contribute to better understanding of the regulatory mechanisms of cotton fiber development. Four miRNAs negatively correlated with fiber length are good candidates for further investigations of miRNA regulation of important genotype dependent fiber traits. Thus, our results will contribute to further studies on the role of miRNAs in cotton fiber development and will provide a tool for fiber improvement through molecular breeding.